The birth of the Viceroyalty Court in Italy and America - Rivero Rodríguez, Manuel (2024)
It has been traditionally argued that the viceroyalty was an institution of Aragonese origin, which evolved over time. This paper presents a different thesis. The vice-royalty was a creation of the administrative and political reforms that took place under Charles V. Based on the ideas and projects of the Great Chancellor Gattinara to deal with the complex governance of a universal Empire, the viceroyalty was configured as a suitable management resource. The viceroyalty, although known and applied in earlier times, took shape at the Cortes of Monzón in 1528 and at the meeting in Genoa in 1529, emerging as the way to govern from a distance and manage the absence of the king. The viceroyalty therefore took on a different dimension from 1529 onwards, or, if you like, it was invented.